The development and application of a technique for continuous measurements of plant elongation : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Botany at Massey University - Marshall, David Clark (Massey University, 1974)
The development of an auxanometer capable of detecting 0.67 um increments in plant elongation and its application to the study of hypocotyl elongation in intact Lupinus angustifolius seedlings is described. A displacement transducer, in conjunction with a carrier wave oscillator-demodulator and a digital voltmeter, was utilised to detect changes in length of the elongating hypocotyls of four day old lupin seedlings. The design of a root bathing solution chamber and environmental control chamber is outlined. With the aid of these two chambers the following environmental parameters could be varied independently:- temperature, water potential and aeration of the root bathing solution; temperature, relative humidity, and gaseous composition of the environment; composition and intensity of light within the environmental chamber. Problems encountered in effecting rapid changes of these parameters are discussed. The viability of the auxanometer as an effective tool for plant growth research was tested by its application to the study of growth rates under a variety of environmental changes. Short term growth responses of lupin hypocotyls to changes in relative humidity, root temperature, and osmotic potential of the root bathing solution, plus exposure to anaerobic nitrogen and carbon dioxide atmospheres, have yielded the following results:- 1. Variations in saturation deficits of between 2.9 and 16.2 mbar altered growth rates only marginally. 2. Fluctuations in root temperatures between 23 and 43°C scarcely effect hypocotyl growth rates. 3. Growth responses to changes in osmotic potential of the root bathing solution are similar to those described by Acevedo et al (1971) with intact maize leaves. 4. Periods of anaerobic nitrogen conditions yielded results comparative with those of Gillbank et al (1972), Who studied the effects of cyanide on growth of wheat coleoptile segments, except for nitrogen treatments of more than 30 minutes in duration. 5. Exposure of seedlings to an anaerobic carbon dioxide atmosphere stimulates hypocotyl growth rates by up to eight times, the results indicating that CO2 stimulates the utilisation of a growth precursor within the cell whilst simultaneously inhibiting its synthesis. The results illustrate both the versatility and the potential of the described auxanometer in the description of plant growth responses to environmental changes, consequently aiding in the identification of the causal mechanisms of plant growth processes.
Keywords: Lupines; Growth (Plants)